2021
DOI: 10.1007/s10943-021-01203-y
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of US Nurses’ Personal Religious and Spiritual Beliefs on Their Mental Well-Being and Burnout: A Path Analysis

Abstract: This study addresses the gap in the literature regarding the impact of nurses' personal religious and spiritual beliefs on their mental well-being and burnout. A model of the association between these factors was tested based on surveys of 207 nurses located in southeastern USA and analyzed to determine the association between religion/spirituality, mental well-being, and burnout. A path analysis supported a model in which, through its positive impact on mental well-being, religion/ spirituality was negatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 69 publications
1
12
0
1
Order By: Relevance
“…Nurses in happy marriages tend to receive important support from their spouse when facing pressures and difficulties (Grover & Helliwell, 2019). Furthermore, the participants with religious beliefs were found to have better overall well-being and physical and mental health than their nonreligious peers, which is consistent with Harris and Tao (2022).…”
Section: Status Of Workplace Burnout Resilience and Well-being In The...mentioning
confidence: 99%
“…Nurses in happy marriages tend to receive important support from their spouse when facing pressures and difficulties (Grover & Helliwell, 2019). Furthermore, the participants with religious beliefs were found to have better overall well-being and physical and mental health than their nonreligious peers, which is consistent with Harris and Tao (2022).…”
Section: Status Of Workplace Burnout Resilience and Well-being In The...mentioning
confidence: 99%
“…Thomas and Barbato ( 2020 ) reported that PRC is negatively correlated with psychological disorders among Christian and Muslim residents of the United Arab Emirates at the time of the COVID‐19 outbreak. Haris and Tao ( 2021 ) provide empirical evidence implying that there is a negative association between PRC and burnout among nurses located in the southeastern United States.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Such strategies included staff recognition boards and increased leadership rounding and support to bring about cultural change 28. Other hospitals and health care institutions have brought attention to the need for self-care and peer care through peer support groups,22 as well as chaplains to provide spiritual or religious care and support 16, 29. Harris and Tao found that being “religious” or “spiritual” has a positive influence on an individual's well-being, while being “nonspiritual” has a negative influence on well-being and burnout 16…”
Section: Anxiety Stress and Burnoutmentioning
confidence: 99%
“…28 Other hospitals and health care institutions have brought attention to the need for self-care and peer care through peer support groups, 22 as well as chaplains to provide spiritual or religious care and support. 16,29 Harris and Tao found that being "religious" or "spiritual" has a positive influence on an individual's wellbeing, while being "nonspiritual" has a negative influence on well-being and burnout. 16 Furthermore, some hospitals have implemented "restorative breaks" in designated calm areas or "zen rooms" as a strategy to reduce stress and fatigue.…”
Section: Effective Holistic Approaches To Reducing Nurse Stress and B...mentioning
confidence: 99%
See 1 more Smart Citation